P639Amiodarone and dronedarone inhibit inwardly rectifying Kir2.1 channels, but not Kir2.2 and Kir2.3 channels. (15th July 2014) - Seyler, C; Xynogalos, P; Scherer, D; Koepple, C; Scholz, EP; Thomas, D; Katus, HA; Zitron, E
Abstract: Background: Cardiac inwardly rectifying IK1 current drives terminal repolarisation. Inhibition of IK1 current can suppress re-entry based arrhythmias and has been demonstrated to exert anti-fibrillatory effects. Human IK1 current is mainly formed by heterotetrameric assembly of three subunits: Kir2.1, Kir2.2 and Kir2.3 channels. Amiodarone and dronedarone have been shown to inhibit cardiac IK1 current, but the molecular basis of these effects has not been elucidated to date. Methods: Human Kir2.1 - Kir2.3 channels were expressed in Xenopus oocytes and current recordings were performed using the double-electrode voltage-clamp technique. Results: Amiodarone and dronedarone exerted differential inhibitory effects on Kir2.1, Kir2.2 and Kir2.3 channels, respectively. Both drugs inhibited only Kir2.1 channels without an effect on Kir2.2 and Kir2.3 channels. We analyzed effects of dronedarone in detail. Onset of inhibition was slow, but the effect was completely reversible upon washout. Biophysical current characteristics such as inwardly-rectifying properties and reversal potential of Kir2.1 currents were not modified. The inhibitory effect did not exhibit frequency dependence. Interestingly, dronedarone inhibited Kir2.1 currents mainly at negative potentials. Conclusions: Amiodarone and dronedarone both inhibit only Kir2.1 channels without affecting Kir2.2 and Kir2.3 channels. In view of the functional significance of Kir2.1 channels, this effect probably underlies the observed inhibition of IK1 current by both compounds and may contribute to their anti-fibrillatory efficacy.